Psychometric evaluation of the Icelandic version of the Insomnia Severity Index (ISI) and the Chalder Fatigue Questionnaire (CFQ) - Sigríður Jóna Sigurjónsdóttir 1966- (2018)
Insomnia and fatigue are common and prevalent problems that have a significant negative consequence for the quality of people’s health and lives. These problems are associated with high health care use and societal cost. There is a need for reliable and valid instruments in screening for problems with sleep and fatigue, that can be used for research and clinical purposes in Iceland. This study examines the psychometric properties of an Icelandic version of the Insomnia Severity Scale (ISI) and the Chalder Fatigue Questionnaire (CFQ), in a group of patients (clinical sample) and students (nonclinical sample). A total number of participants were 143 in two samples, 95 females and 48 males with age range from 18 years to 64 years (M = 30.4, SD, 13.79). The clinical sample (n = 50), came from Reykjalundur Rehabilitation Center in Mosfellsbær and the participants in the non-clinical sample (n = 93) came from Reykjavík University. Results show that the scales are reliable (ISI, α =.87 and CFQ, α =.94), they have good convergent validity and discriminate between clinical and non-clinical samples. Factor Analysis (Maximum Likelihood ML) on the ISI, revealed a one factor loading explaining the highest variance in both samples. For the CFQ, a Principal Component Analysis (PCA) confirmed two component loadings in the clinical sample but only one component of in the non-clinical sample. The psychometric properties of the Icelandic version of the ISI and the CFQ have been shown to be adequate and the results suggest that they can be used for research and in clinical work. Keywords: Insomnia, fatigue, measurement scale